1, 8‐Dioxyanthracene‐Derived Crown Ethers: Synthesis, Complexation with Paraquat and Assembly of a Tetracationic Cyclophane‐Crown Ether Based [2]Catenane. Issue 31 (19th September 2014) - Tang, Bo; Yang, Hong‐Mei; Hu, Wen‐Jing; Ma, Ming‐Liang; Liu, Yahu A.; Li, Jiu‐Sheng; Jiang, Biao; Wen, Ke
Abstract: 1, 8‐Dioxyanthracene‐based bisarylene crown ethers, composed of ethylene glycol chains and aromatic moieties, have been synthesized. Complexation studies revealed that these crown ethers could form 1:1 complexes with methyl viologen dication ( N, N′ ‐dimethyl‐4, 4′‐bipyridinium dication; MV 2+ ) in a mixed solvent of CDCl3 and CD3 CN (1:1 v/v) with association constants in a range of (1.2 ± 0.1) × 10 3 M –1 to (1.6 ± 0.2) × 10 4 M –1 . The structure of the complex and the strength of the π‐donor/π‐acceptor interactions between the 1, 8‐dioxyanthracene planes and the pyridinium rings of MV 2+ are highly dependent on the length of the polyether chains of the ethers. Structural analysis showed that the tetraethylene glycol‐derived bis‐1, 8‐dioxyanthracene‐based crown ether9 forms a U‐shaped host‐guest complex with MV 2+ by inserting the coplanar pyridinium rings of MV 2+ between the two parallel oriented 1, 8‐dioxyanthracene units of9, which is driven predominantly by π‐donor/π‐acceptor interactions. The pentaethylene glycol‐derived bis‐1, 8‐dioxyanthracene‐based crown ether10, however, adopts a crescent‐shaped conformation in complex10 ⊃MV 2+ with the MV 2+ guest being encapsulated by the polyether chains, propelled mainly by the hydrogen‐bonding interactions between the hydrogen atoms of MV 2+ and the oxygen atoms of the polyether chains of10 . Similarly, the hexaethylene glycol‐derived bis‐1, 8‐dioxyanthracene‐based crown ether11 forms a complex with MV 2+ . However, only weak π‐donor/π‐acceptor interactions between the aromatic groups of the mixed bisarylene crown ethers12 and13, and MV 2+ were observed, and construction of tetracationic cyclophane [CBPQT 4+ ] and crown ether13 based [2]catenane15 was achieved through supramolecular interactions between the [CBPQT 4+ ] ring and naphtho unit in the crown ether. Abstract : Sandwich and crescent conformations were adopted by bis‐1, 8‐dioxyanthracene‐based crown ethers upon complexation with methyl viologen dication (see Scheme). The structure of the complexes are highly dependent on the length of polyether chains of the crown ethers.